A Pilot Study on the Response of Overweight Students to the Design of Two Different Types of Tai Chi Training Programs and Data Quality Control - Yantao Niu; Rojapon Buranarugsa; Piyathida Kuhirunyaratn (Integrative Medicine Reports)
Aim: The objectives of this study were to evaluate the responses of overweight college students to two types of Tai Chi intervention programs, to ensure data quality by assessing repeatability and reliability, and to assess changes in variable means after training. Additionally, the study aimed to compare the exercise intensity between the two types of Tai Chi during 30 min of practice. Methods: Participants underwent a 2-week Tai Chi intervention program, consisting of 1-h sessions, three times a week. Measurements of heart rate (HR) and energy expenditure were obtained using a Polar heart rate monitor (H10), while flexibility, upper and lower limb strength, balance, and aerobic endurance were measured before and after the intervention. Repeatability was established using Bland-Altman plots, and reliability was assessed using intraclass correlation coefficient (ICC). Between-group variables were compared using independent t-tests, while paired t-tests were used to compare changes within each group between pre- and post-tests in the mean of variables. Results: Bland-Altman plots showed good repeatability of pre- and post-test and ICC values for all measured variables ranging from 0.54 to 0.99. There were no significant changes observed in the mean of all measured variables from pre- to post-testing in both groups (p > 0.05). Significant difference was observed in metablic equivalent (MET) value (5.75 ± 0.66 vs. 4.65 ± 0.40) and maximum HR (141.80 ± 10.83 vs. 117.50 ± 10.97) between the two different types of Tai Chi in 30 min of Tai Chi practice (p < 0.001). Conclusions: The training and assessments were safe and appropriate for overweight Chinese male college students, and the measurement methods used in the study were reliable. A 2-week Tai Chi training did not result in changes in the mean of variables. The study suggests the possibility of further research under well-designed training programs and close supervision by researchers. Clinical Trials Registry Identifier ChiCTR2200059427; April 29, 2022.